Dynamic failure and stability model analysis of thick and hard rock with wedge-structure immediate roof occurrence - Zhao, Tong; Gong, Peilin; Yetilmezsoy, Kaan; Bahramian, Majid; Liu, Changyou (SPRINGER HEIDELBERG, 2021)
To eliminate roof-control disasters typically encountering in mines with thick and hard rock strata, fracture characteristics, instability mechanism and prevention methods were investigated in the study. A mine stope with thick and hard main roof and wedge-structure immediate roof in Zhuxianzhuang Coal Mine was taken as the background. In terms of the strata behaviors and roof control difficulty levels via physical simulations, mining zones were classified into strong pressure behavior zone, less-strong pressure behavior zone and pressure mitigation zone. Theoretical analysis was used to study the interaction characteristics of the support-surrounding rock under different mining zones and the principles and methods of zonal control under THR were proposed. A coordinated control method, which combined confined blasting in water-filled deep holes for reducing the roof fracture size and reasonable support optimization for increasing the supporting intensity, was applied to the strong pressure behavior zone and less-strong pressure behavior zone. The mechanical calculation model of a presplit-THR-block-immediate-roof-top-block-top-coal-wall-hydraulic-support system was established, which determined the length of confined blasting blocks as 20-25 m and supporting intensity as 1.15-1.28 MPa. These parameters can satisfy the requirements of THR control and lead to the best economic performance.
Keywords: Thick and hard roof; Wedge-structure immediate roof; Dynamic failure and stability mode analysis; Mining zones; Collaborative control; PRESSURE RELIEF; EXTRACTION; MECHANISM; Energy & Fuels; Engineering; Geology